2021
DOI: 10.1177/0271678x211020865
|View full text |Cite
|
Sign up to set email alerts
|

Role of platelets in the pathogenesis of delayed injury after subarachnoid hemorrhage

Abstract: Aneurysmal subarachnoid hemorrhage (aSAH) patients develop delayed cerebral ischemia and delayed deficits (DCI) within 2 weeks of aneurysm rupture at a rate of approximately 30%. DCI is a major contributor to morbidity and mortality after SAH. The cause of DCI is multi-factorial with contributions from microthrombi, blood vessel constriction, inflammation, and cortical spreading depolarizations. Platelets play central roles in hemostasis, inflammation, and vascular function. Within this review, we examine the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 110 publications
(190 reference statements)
0
11
0
Order By: Relevance
“…Prior statin was associated with reduced proportion of evacuation of intracranial hematoma without increasing mortality during in-hospitalization. 26 The cost-effectiveness ratio of anticoagulant therapy is still uncertain in ICH and more investigations are warranted, 27,28 as well as the role of platelets and onset time that have been studied in subarachnoid hemorrhage 29 and ischemic stroke. 30 Several limitations need to be paid attention to in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Prior statin was associated with reduced proportion of evacuation of intracranial hematoma without increasing mortality during in-hospitalization. 26 The cost-effectiveness ratio of anticoagulant therapy is still uncertain in ICH and more investigations are warranted, 27,28 as well as the role of platelets and onset time that have been studied in subarachnoid hemorrhage 29 and ischemic stroke. 30 Several limitations need to be paid attention to in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have indicated that microthrombi formation in the distal vessel after aneurysmal SAH (aSAH) is involved in the development of DCI [39]. Such as Hb, platelets extravasated after SAH may play a role in vessel constriction and thrombosis occurrence [40]. Platelets interact with endothelial cells and participate in the inflammation cascade through the release of extracellular vesicles containing chemokines/cytokines [41].…”
Section: Hemoglobin Degradation Product and Plateletmentioning
confidence: 99%
“…Platelets/microthrombi are found near arteries experiencing vasospasm [42,43]. The mechanism by which platelets induce large artery vasospasm is related to the release of elevated levels of vasoactive thromboxane A2 (TXA2) and Platelet-Derived Growth Factor-b (PDGF) as highlighted by a number of clinical studies [40,[44][45][46]. Cisternal level of PDGF-b after SAH has also been reported to positively correlate with the incidence and severity of vasospasm [45].…”
Section: Hemoglobin Degradation Product and Plateletmentioning
confidence: 99%
“…After microvasospasms in the compensation period, platelet aggregation 20 and leukocyte plugging 21 in capillaries cause microcirculatory dysfunction in the decompensation phase. When the microthrombi fill microvessels 22 and impair the glymphatic drainage system, 23 the whole microcirculation collapses without blood flow, and microcirculatory dysfunction moves into an irreversible phase. Recent findings involving neutrophil extracellular traps (NETs) 24 released from neutrophils after SAH might represent important intersections amongst platelet aggregation, microthrombosis, and microglia-mediated inflammation, 25 further supporting the pathophysiological characteristics of the irreversible phase of microcirculation.…”
Section: Intersections In the Pathophysiological Changes Induced By T...mentioning
confidence: 99%